Extreme Storm Surge Events and Associated Dynamics in the North Atlantic - Barbot, Simon; Pineau-guillou, Lucia; Delouis, Jean Marc (Journal of Geophysical Research: Oceans, 2024)
Storm surges events are investigated using the ECHAR method, which identifies and quantifies the different dynamical structures of a typical storm surge event. In the North Atlantic, analysis of 65 tide gauges revealed that storm surge events display two major and two minor structures, each of them corresponding to specific ocean dynamics. The two major structures refer to a slow-time Gaussian structure, lasting around 24 days, associated with the impact of the atmospheric pressure and a fast-time Laplace structure, lasting around 1.4 days, mainly wind-driven. The absence of the Gaussian structure along the North America coasts is explained by storms of smaller spatial extension, compared to Europe. Concerning the minor structures, a negative surge of around 6 cm just after the peak surge is observed over North America only. Such a sudden drop of the sea level is explained by the turning winds during the storm event, favored by the smaller spatial extension of storms. Finally, high frequency oscillations, with amplitude typically of 3 cm and up to 25 cm, are observed at some tide gauges. These oscillations refer to tide-surge interactions and they are often maximum at a specific phase of the tide and/or enhanced because of resonant basins.